Subcritical water extraction process for microalgal biodiesel production - Thiruvenkadam, Selvakumar (2020)
Microalgae have been used as a substrate for biodiesel production due to their numerous advantages, including fast growth rate, non-edibility, and the ability to accumulate substantial amounts of carbohydrates, lipids, and proteins. However, current extraction technologies used to produce oil from microalgal biomass are expensive, unsustainable, involve lengthy processing steps and result in lower product yields. One of the newer extraction techniques is subcritical water extraction which offers lower production costs, milder operating conditions, and a shorter production period compared to other conventional methods, such as chemical and biological extraction. The current subcritical water extraction (SCW) for biodiesel production involves two steps: extraction and transesterification. These two steps can be combined in one-step by the proposed subcritical methanol extraction (SCM) process for microalgal biodiesel production. In this study, SCW and SCM were used to treat Chlorella pyrenoidosa. The operational factors such as reaction temperature, reaction time and biomass loading influence the oil yield during the extraction process. In this study, response surface methodology was employed to identify the desired extraction conditions for maximum extraction yield. SCW experiments were carried out in batch reactors as per the central composite design with three independent factors: reaction temperature (170 to 370 °C), reaction time (1 to 20 min) and biomass loading (1 to 15%). The maximum oil yield of 12.89 wt.% was obtained at 320 °C and 15 min, with 3% biomass loading. Sequential model tests showed the good fit of experimental data to the second-order quadratic model. The extracted oil from SCW is converted to biodiesel via second-step, transesterification. Recent developments in subcritical studies utilize subcritical alcohol solvents as a single step process to produce biodiesel from algae. Here, the algal biomass is subjected to SCM in the second phase of this study. The effects of three operational factors: reaction temperature (140 to 220 °C), reaction time (1 to 15 min) and methanol to algae ratio (1 to 9 wt.%) were investigated. A maximum yield of crude biodiesel of 7.1 wt.% was obtained at 160 °C, 3 min reaction time and 7 wt.% methanol to algae ratio. The analysis of variance revealed that methanol to algae ratio is the most significant factor for maximizing biodiesel yield. Regression analysis showed a good fit of the experimental data to the second-order polynomial model. Higher cetane number (74.92) and low iodine value (58.81 g I2/100 g) crude biodiesel produced from SCM were found in compliance with the European standard (EN 14214). The SCW and SCM experimental data were fitted with three models, namely first-order kinetic model, second-order kinetic model and Fick’s law kinetic model. A comparison between SCW and SCM in terms of mass flow and energy consumption is provided through the LCA study. In terms of energy requirements, SCM has a lower energy demand than SCW. The use of subcritical technology for high-grade algal biodiesel production is expected to be promising and will result in a positive outlook for commercially viable production of high-quality biodiesel.